The Czech Republic on its way towards the West European structures - KULTALAHTI, Olli; KARPPI, J. llari; RANT ALA, Heikki (European Spatial Research and Policy, 1997)
This paper studies social, economic and other developmental trends in the Baltic countries: Estonia, Latvia and Lithuania, after the collapse of the Communist rule in 1991 . Attention is paid to some essential changes in the transition from the centrally planned economy towards a market economy. The Baltic Region has been seen from outside as more solid than it is in reality. The Baltic countries differ from each other in many respects. For example, there are differences in privatisation processes. In Estonia the economic development has been faster than in the other two Republics. All three countries have applied for European Union membership. Although the economies of the Baltic countries have come rather close to an industrial structure prevailing in the market economy, the qualification for membership stili implies a great amount of catching up.